Cobertura mediática de los mass media radiales y televisivos guayaquileños ante desastres naturales - Aguilar Alcívar, Carlos Alberto (2018)
The earthquake of April 16, 2016 highlighted the lack of preparation that journalists have when carrying out coverage of this magnitude; radio and television media did not meet the information needs of the Ecuadorian citizens; the obligation of the media is to inform timely, contextualized and with official data of the National Secretariat of Risk Management (SNGR), the present investigation covers the behavior and interaction presented by two media of radio and television nature and its influence of contents in the transmission of informative notes before the natural disaster that occurred in the provinces of Manabí and Esmeraldas, the research is of mixed or dual focus, applying investigative collection techniques based on these two approaches; the various notes issued by the media that stand out as objects of study were monitored, contrasting with the citizenship the impact of these publications on their daily development and activity. As a result, it is sought to identify which procedures were what stood out in this process directly or indirectly and what kind of repercussions they caused in the collective Guayaquil citizens……